Preoperative evaluation of microvascular invasion with circulating tumour DNA in operable hepatocellular carcinoma. (23rd May 2020) - Wang, Dong; Xu, Yaping; Goldstein, Jennifer B.; Ye, Ke; Hu, Xi; Xiao, Liang; Li, Lifeng; Chang, Lianpeng; Guan, Yanfang; Long, Guo; He, Qiongzhi; Yi, Xin; et al.
Abstract: Background & Aims: Microvascular invasion (MVI) is a critical prognostic factor for operable hepatocellular carcinoma (HCC). This study aimed to explore the performance of circulating tumour DNA (ctDNA) in evaluating MVI status preoperatively. Methods: Seventy‐three HCC patients were enrolled and randomly divided into a training cohort and a validation cohort in a 2:1 ratio, and preoperative blood and surgical tissue samples were obtained. Genomic alterations were analysed using targeted deep sequencing with a 1021‐gene panel. Results: In training cohort, 260 somatic mutations were identified in 40 blood samples (81.6%). CtDNA mutation was verified in paired tissue sample in 39 patients (97.5%). In univariate analysis, ctDNA allele frequency (AF) and largest tumour diameter were associated with the presence of MVI, but ctDNA AF was the only independent risk factor in multivariate analysis. With the cut‐off value of 0.83%, ctDNA AF determined the presence of MVI with the sensitivity of 89.7% and specificity of 80.0% in the training cohort, and the sensitivity of 78.6% and the specificity of 81.8% in the validation cohort. In preoperative evaluation, ctDNA AF, AFP level and BCLC staging were associated with recurrence‐free survival in both univariate and multivariate analysis. Conclusions: CtDNA can serve as an independent risk factor of MVI for operable HCC and help determining precise treatment strategies. The integration of ctDNA in the management of operable HCC may achieve better clinical outcomes.